Postemotional Law - S. G. Mestrovic (Law Text Culture, 2000)
How can one begin to make sense of the state of law in the present fin de millennium? Is law still on the trajectory of the socalled Enlightenment project? Is it a social institution which, in tandem with others, promotes progress, justice, and the triumph of reason over tradition and ignorance (see Gellner 1992)? Or, at the other extreme, has law also become postmodern? Such that, as truth becomes subjective, law becomes an empty gesture, reduced to a rootless, circulating fiction, along with other such fictions that are consumed by the nihilistic masses (see Rosenau 1992)? In this paper, I will argue for a middle characterization; one based on my book, Postemotional Society (1997), and that I call postemotional law.